Pandangan Terhadap Disabilitas: Upaya Menjadikan Gereja Inklusi - Kezia Luciana Mongi (Institut Agama Kristen Negeri Tarutung, 2022)
This work aims to share theological thoughts about people with disabilities based on the Bible. Using a qualitative, non-experimental concept, the author accumulated information by studying the Systematic Dogma. From the Dogma of God, the result is that people, including people with disabilities, are God's creation. The person of God is a person who is perfect and omni present. The study of the Dogma on the person led to the idea that man is the Imago Dei, who was built by God Himself. Sin cannot be looked at from physical deficiencies as some people think, because real sin is disobedience to God which causes human separation from God. This is what Jesus brings to His work of salvation, which is to achieve the healing of the bond between man and God. In this case the church needs to actively carry out its function and calling, especially koinonia and diakonia, so that all people, including those with disabilities, continue to be in hope of a glorified body. Applications that must be tried in the church community are to view people with disabilities appropriately, share good learning, serve and share service space with people with disabilities.